Application of natural antioxidants from traditional Chinese medicine in the treatment of spinal cord injury - Huang, Zhihua; Wang, Jingyi; Li, Chun; Zheng, Weihong; He, Junyuan; Wu, Ziguang; Tang, Jianbang (Frontiers in Pharmacology, 2022)
Spinal cord injury (SCI) is a devastating central nervous system disease, caused by physical traumas. With the characteristic of high disability rate, catastrophic dysfunction, and enormous burden on the patient’s family, SCI has become a tough neurological problem without efficient treatments. Contemporarily, the pathophysiology of SCI comprises complicated and underlying mechanisms, in which oxidative stress (OS) may play a critical role in contributing to a cascade of secondary injuries. OS substantively leads to ion imbalance, lipid peroxidation, inflammatory cell infiltration, mitochondrial disorder, and neuronal dysfunction. Hence, seeking the therapeutic intervention of alleviating OS and appropriate antioxidants is an essential clinical strategy. Previous studies have reported that traditional Chinese medicine (TCM) has antioxidant, anti-inflammatory, antiapoptotic and neuroprotective effects on alleviating SCI. Notably, the antioxidant effects of some monomers and compounds of TCM have obtained numerous verifications, suggesting a potential therapeutic strategy for SCI. This review aims at investigating the mechanisms of OS in SCI and highlighting some TCM with antioxidant capacity used in the treatment of SCI.